Parental feeding practice is associated with child's body mass index in Thai school-aged children: A case study in Don Tum district, Nakhon Pathom, Thailand - Uruwan Yamborisut; Piyanuch Visetchart; Wiyada Thasanasuwan; Weerachat Srichan; Rittirong Unjana (College of Public Health Sciences, Chulalongkorn University, 2018)
Purpose - Parental feeding practice (PFP) plays an important role in child's eating behavior and weight status, but less information is available about its role in the Thai family setting. The purpose of this paper is to examine the influence of PFP on child's gender and body mass index (BMI). Design/methodology/approach - Participants included 227 parents-child dyads from the suburban area of Nakhon Pathom province, Thailand. Children aged 9-12 years and parents who were either child's mother, father or grandfather/grandmother were enrolled in the study. Body weight, height, waist circumference and body fat were measured in all children. Eating behavior of each child was assessed by using child's eating questionnaire. Parents also provided their feeding practices in child feeding questionnaires. Information on household food security was also obtained from children's parents. Findings - There was significant difference in eating behaviors and home environment between child's genders. For child's eating behavior, mean total eating scores of girls were significantly greater (p=0.002) than that of boys and that the inappropriate home environment was more found in families of boys than girls. Regarding feeding practice, parents used more food restriction (p=0.008) and monitoring on child's eating (p=0.042) in girls than boys. Parents put more pressure to eat on the normal weight than obese children (p=0.001). Regression analysis revealed that, apart from parental BMI and household income, PFPs have a significant impact (15.6 percent explained variance) on child's BMI. Originality/value - This study highlights the importance of being aware of child's gender and weight status when feeding practices were provided to them. Nutrition education for parents should take account for parents' perceptions and concerns as well as the modification of feeding practices to improve children's eating behaviors.